2021
DOI: 10.3390/ijms22179185
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Biomarkers in Colorectal Cancer

Abstract: The cellular microenvironment composition and changes therein play an extremely important role in cancer development. Changes in the extracellular matrix (ECM), which constitutes a majority of the tumor stroma, significantly contribute to the development of the tumor microenvironment. These alterations within the ECM and formation of the tumor microenvironment ultimately lead to tumor development, invasion, and metastasis. The ECM is composed of various molecules such as collagen, elastin, laminin, fibronectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 208 publications
(309 reference statements)
1
21
0
Order By: Relevance
“…Laminins are also involved in cancer progression, including invasion, migration, angiogenesis, metastasis and drug resistance [ 149 , 150 , 151 ]. Expression of various laminin subunits is often upregulated in tumor or stromal cells of malignant tissues.…”
Section: Ecm Remodeling and Modification In Cancermentioning
confidence: 99%
“…Laminins are also involved in cancer progression, including invasion, migration, angiogenesis, metastasis and drug resistance [ 149 , 150 , 151 ]. Expression of various laminin subunits is often upregulated in tumor or stromal cells of malignant tissues.…”
Section: Ecm Remodeling and Modification In Cancermentioning
confidence: 99%
“…Studies have implicated the dysregulation of ECM components in OV tumorigenesis and progression and suggested that the elucidation of ECM function in OV is important for developing effective biomarkers and novel drugs ( 53 57 ). Studies have also shown that the potential biomarkers of OV metastasis are enriched in ECM-receptor interaction pathway ( 57 ) among other pathways including PI3K/Akt signaling pathway which was also found implicated in the inositol phosphate metabolism as described above. ECM-receptor interaction pathway was also incriminated in the survival and prognosis of high-grade serous OV patients ( 58 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the GO functional enrichment results, most of these genes were clustered in functional groups related to the extracellular matrix (ECM). The ECM, as the main component of the tumor microenvironment, is considered to play a leading role in the progression of various cancers, including CRC, and promotes the invasion and metastasis of cancer ( 41 43 ). In addition, Ortensi et al have demonstrated that the stemness characteristic of cancer tissue contributes to glioma invasiveness, which is closely related to the ECM ( 44 ).…”
Section: Discussionmentioning
confidence: 99%